Smart Power Grids 2011 - Keyhani, Ali.; Marwali, Muhammad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Electric power systems are experiencing significant changes at the worldwide scale in order to become cleaner, smarter, and more reliable. This edited book examines a wide range of topics related to these changes, which are primarily caused by the introduction of information technologies, renewable energy penetration, digitalized equipment, new operational strategies, and so forth. The emphasis will be put on the modeling and control of smart grid systems. The book addresses research topics such as high efficiency transforrmers, wind turbines and generators, fuel cells, or high speed turbines and generators.
I. Modeling of Smart Grids -- Loads Impedance model, P and Q model, load forecasting -- High Efficiency transformers -- PV Sources( Thermal and PV panels) -- Wind Turbines -- Wind Generators -- High Speed Micro turbines -- High Speed Micro generators -- Fuel Cells -- DC/DC Converters -- Bidirectional DC-DC Converters -- Storage systems ( Battery and Fly wheels) -- AC/DC rectifiers -- DC/AC Inverters -- Multi Level Converters -- Bidirectional Converters -- II. Control of Smart Grid Systems -- Smart Meters -- Micro grids -- Control of DC/DC Converters -- Control of DC/AC inverters -- Load Frequency Control in Micro Grid Systems -- Voltage Control in Micro Grid system -- Active and Reactive Power Control -- Load Control in Micro Grid Systems -- Synchronized operation of Micro Grids -- Islanding Operation of Micro Grids -- Cyber Control of Micro Grid Systems -- Design High MW PV Systems -- Design of high Power Wind Farm -- Control of Smart Grid System with high green energy penetration.
Keywords: Engineering; Artificial intelligence; Production of electric energy or power; Renewable energy sources; Engineering; Power Electronics, Electrical Machines and Networks; Renewable and Green Energy; Computational Intelligence; Artificial Intelligence (incl. Robotics).